Comparative Study of Puntius chola Process Quality from Fresh to Dried Forms - Subal Kumar Ghosh; Rupali Das; Pritam Tripathy; Hauzoukim; Sambid Swain (Journal of Indian Fisheries Association, 2023)
The present work aims to assess the quality of Puntius chola in a fresh and dried form to understand the changes in specific nutrients in two different forms of consumption. In fresh and dried samples, the primary (PV) and secondary (TBARs) lipid oxidative degradation products ranged from 2.61 to 29.62 and 0.87 to 3.29, suggesting dried sample quality within the acceptable range. pH and TVBN changes were within the acceptable ranges for fresh (6.94 to 6.66) and dried samples (13.07 to 44.25 mg nitrogen/100g). Redness (a*) grew from fresh to dried sample whereas the lightness (L*) value steadily dropped. Both sample TPC and TFC (log cfu/g) levels were found to be within safe limits. Overall acceptability ratings for the fresh fish (7.0 ±0.28) were higher than dried (5.25 ±0.26) fish products. However, the flavor of dried fish has a greater impact on the local tribal populations than that of fresh fish. The nutritional, biochemical, and microbiological quality of dried fish"Sukhua" indicate it is safe for consumption and a rich source of nutrients.